Enhanced Antibacterial and Antioxidant Properties of Chitosan Films Blended with Gallic Acid and Incorporated with Thymol Silver Nanoparticles - Lade, Bipin; Kamdi, Akash; Shanware, Arti (Journal of Drug Delivery and Therapeutics, 2021)
In the present study, an attempt has been made to build and evaluate Chitosan+Glycerol/Gallic acid/Thymol-silver nanoparticles or chitosan blended (C+G/GA/T-SNPs) film to significantly improve antioxidant and antibacterial activity for accelerated wound healing. Methanolic Gallic acid is used for the first time in antibacterial chitosan control (C+G) films. All developed films, compounds was Thymol and Gallic acid and their synthesized Thymol silver nanoparticles (T-SNPs) and Gallic acid silver nanoparticles (GA-SNPs) were characterized by Fourier-transform infrared spectroscopy (FT-IR), Scanning electron microscopy (SEM), X-Ray diffraction (XRD), Zeta potential (ZP), Dynamic light scattering (DLS), and UV-Vis spectroscopy. T-SNPs and GA-SNPs are rod and spherical in shape and were sufficient to reduce, capped, and stabilize. T-SNPs and GA-SNPs were measured Dynamic Light scattering and found to be 123.2 nm and 121.1 nm with surface charges of -19.7 and -20.3 respectively. The incorporation of methanolic Gallic acid and T-SNPs into chitosan films, as predicted, effectively enhanced antioxidant and antimicrobial activity. The antimicrobial activity of Thymol, T-SNPs and C+G/GA/T-SNPs film showed more zone of inhibition than Gallic acid, GA-SNPs and C+G film. The elasticity, texture and folding endurance of the C+G film and C+G/GA/T-SNPs films have been substantially improved. The ecological quality of the generated C+G and C+G/GA/T-SNPs film was determined by the assessment of soil degradation and water degradation parameters. These findings lead to the conclusion that the C+G/GA/T-SNPs film produced with Gallic acid and T-SNPs can improve wound healing. Keywords: Chitosan, Gallic Acid, Thymol Silver Nanoparticles, Antibacterial and Antioxidant Properties.